A Material Quest for Low Cost, High Efficiency, Stable Solar Cell: A Review - Namita Rajput (International Journal of Advanced Science and Technology, 2022)
In the present paper PSCs (perovskite solar cells) are investigated as one of the most hopeful photovoltaic technologies currently being developed. Perovskite solar cells have increased their photoelectric power conversion efficiency from 3.8 percent to 25.2 percent in less than a decade, making them the greatest contender for the next generation of solar cells to replace regular silicon solar cells. Furthermore, using PSCs in tandem solar cells, whether in a 4-terminal or monolithic form, can significantly improve conversion efficiency. Despite their excellent characteristics, PSCs have experienced a number of obstacles, including deterioration in the presence of moisture, oxygen, and UV, toxicity, and others, which have hampered the commercialization of perovskite technology. This study reviews recent exciting developments in perovskite solar cells and discusses the underlying principles of perovskite materials in solar cells, as well as their structural evolution, stability difficulties, and potential solutions.